Turbine Generator efficiency analysis in Geothermal Power Plant PT Geodipa Energi Unit Dieng. - Qurrahman, Alfian Hardi; Wilopo, Wahyu; Bayu, Himawan Tri (Sekolah Tinggi Teknologi Adisutjipto, 2019)
The Geothermal power plant at PT Geodipa Dieng has been operating for more than 10 years. It has undergone for several improvements including the replacement of turbines where to increase turbine efficiency. Before changing the turbine, the efficiency of turbine has decreased due to several factors, such as decrease in load, maintenance, usage, the lifetime etc. Therefore it needs to be analyzed the effiency of the turbine to find out whether the turbine is still feasible or not, and to find out whether it has necessary to replace the turbine again. The result of the turbine generator efficiency are obtained in one year from April 2017 to March 2018 with an average value of 70-85%. Based on the literature, the value is still at the turbine efficiency standard in general, which is 60-80%. So the turbines can still be categorized reliably and do not need to be changed.